Do Hippocampal Neurons Really Count for Comorbid Depression in Patients With Mesial Temporal Lobe Epilepsy and Hippocampal Sclerosis? A Histopathological Study - Visoná de Figueiredo, Nathália Stela; Jardim, Anaclara Prada; Mazetto, Lenon; Corso Duarte, Jeana Torres; Comper, Sandra Mara; Alonso, Neide Barreira; da Silva Noffs, Maria Helena; Scorza, Carla Alessandra; Cavalheiro, Esper Abrão; Centeno, Ricardo Silva; de Araújo Filho, Gerardo Maria; Yacubian, Elza Márcia Targas (Frontiers in Integrative Neuroscience, 2021)
Depression is the most frequent psychiatric comorbidity seen in mesial temporal lobe epilepsy (MTLE) patients with hippocampal sclerosis (HS). Moreover, the HS is the most frequent pathological hallmark in MTLE-HS. Although there is a well-documented hippocampal volumetric reduction in imaging studies of patients with major depressive disorder, in epilepsy with comorbid depression, the true role of the hippocampus is not entirely understood. This study aims to verify if patients with unilateral MTLE-HS and the co-occurrence of depression have differences in neuronal density of the hippocampal sectors CA1 to CA4. For this purpose, we used a histopathological approach. This was a pioneering study with patients having both clinical disorders. However, we found no difference in hippocampal neuronal density when depression co-occurs in patients with epilepsy. In this series, CA1 had the lowest counting in both groups, and HS ILAE Type 1 was the most prevalent. More studies using histological assessments are needed to clarify the physiopathology of depression in MTLE-HS.